Experimental research on the dynamic thermal performance of a novel triple-pane building window filled with PCM. (November 2016) - Li, Shuhong; Sun, Gaofeng; Zou, Kaikai; Zhang, Xiaosong
Abstract: Phase change material (PCM) filled window shows significances in the building energy consumption. Recent researches on the double-pane window filled with PCM (DW + PCM) show that in summer, the released latent heat from PCM into the room during summer night is considerable as well as the overheating risk from the completely melted PCM is non-ignorable, both of which have adverse effects on the building insulation performance. In order to solve the problems, a configuration of triple-pane window (TW + PCM), the outer cavity of which is filled with PCM, is proposed in this paper. Experiment to investigate the thermal performance of TW + PCM is conducted in the summer days. Experimental systems of two reference windows (DW + PCM and triple-pane window (TW)) are also set up successively. The results show that compared with DW + PCM and TW, the peak temperature on the interior surface of TW + PCM reduces by 2.7 °C and 5.5 °C respectively, which means the overheating risk is avoided effectively, and heat entered the building through the TW + PCM reduces by 16.6% and 28% respectively in the sunny summer day. In the rainy summer day, the TW + PCM shows advantageous performance on reducing the temperature fluctuation of the interior surface and the heat entered the building.